A New Method for Stator Ground Fault Protection with Voltage Injection on Large Hydro Generators Grounded by Arc Suppression Coils - Lang ZHOU; Jianzheng LIU; Qixue ZHANG; Bo ZHONG; Lin GUI (Zhongguo dianli)
For stator ground fault protection of large hydro-generators grounded with arc suppression coil at neutral point, the conventional method is to inject 20 Hz signal from the instrument coil attached to the arc suppression coil. In order to improve the effect of the protection and to overcome the difficulties caused by the increase of stator-to-ground capacitance, a new method is proposed to inject the 20 Hz signal from the resistor in series with the arc suppression coil. The proposed method is compared with the conventional one in terms of the 20 Hz equivalent circuit viewed from the injection port, and the corresponding calculation method for transition resistance is also studied. Taking a generator of Tianshengqiao-Ⅱ Hydro Power Station as the research object, an arc suppression coil based on the parameters of the real generators’ arc suppression coil is customized for test, and the stator ground fault experiment is conducted on a dynamic simulation generator to test the effectiveness of the two methods. The results of the experiment show that, compared with the conventional method, the proposed new method has the maximum measured ground fault transition resistance increasing from 5.6 kΩ to 20 kΩ with an error within ±6%.